Knowledge, Attitudes and Practices Related to Viral Hepatitis Among Professionals in a Brazilian Health Foundation - Scarponi, Cristiane Faria Oliveira; Souza-Silva, Gabriel; Mol, Marcos Paulo Gomes (Fronteira: Journal of Social, Technological and Environmental Science, 2024)
Awareness of viral hepatitis is a key factor in the suppression of this health condition, particularly among healthcare professionals. This study aimed to evaluate the level of knowledge, attitudes, and practices related to viral hepatitis in a Brazilian public health foundation. A self-administered questionnaire, addressing was electronically available to all professionals in December 2020. Descriptive and inferential analyses were performed using OpenEpi software. The response rate of the viral hepatitis questionnaire was 99.2%. The accuracy index for knowledge was less than 70%, encompassing basic concepts, modes of transmission, and vaccination. Most professionals reported accurate preventive attitudes, except for the decontamination of work surfaces, hygiene, and cooking of food. A high rate of unsafe actions was identified, such as engaging in unprotected sex, sharing personal objects when caring for nails, incomplete use of personal protective equipment, and incomplete vaccination. There is a general lack of awareness regarding viral hepatitis, especially among healthcare professionals. The poor understanding of risks and prevention methods has led many professionals to act imprudently or negligently. These findings provide concrete subsidies for the formulation of more effective educational actions and institutional training, given that the mere provision of information does not produce effective changes in professional behavior.